A Program for Elementary School Education The Intergroup Relations Curriculum; Volumes I and II - Gibson, John S.; Tufts Univ., Medford, MA. Lincoln Filene Center for Citizenship and Public Affairs ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1969)
These two volumes update, through September 1968, the intergroup relations curriculum begun in 1963 by the Lincoln Filene Center with the aim of helping elementary students (grades 1-6) not to prejudge people different from themselves. Volume 1 begins with a description of the projects's background (see ED 010 029 and ED 016 552) and research support for the Center's fundamental idea that the major thrust for improving democratic intergroup relations must be in elementary schools and that, while it is not being done, specific and tested approaches are available. Also in volume 1 are descriptions and evaluations of the Center's six 1968 inservice programs for 350 teachers and a substantial section on procedures for evaluating elementary students. The major portion of volume 2 is comprised of 20 learning activities (such as "Skin Color" and "Demonstrations") and two instructional units on the American Indian and Declaration of Independence, which can be incorporated into fourth through sixth grade social studies. Volume 2 also contains a pedagogical guide for using the curriculum, a detailed explanation of the conceptual framework (the "governing process"), and five methodological tools (similarities; differences; interactions; ideals, myths, realities; "here and now") for teaching the curriculum. The report projects more emphasis on student evaluation and preservice education for 1969. A 265-item bibliography of instructional resources for teachers and students is included. (LP)
Availability: Lincoln Filene Center for Citizenship and Public Affairs, Tufts University, Medford, Massachusetts ($5.00).
Contract Number: OEG-1-8-080197-001-057.
Sponsoring Agency: Office of Education (DHEW), Washington, DC. Bureau of Research.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: American Indians; Elementary School Teachers; Evaluation Methods; Inservice Education; Instructional Materials; Learning Activities; Student Evaluation; Teaching Methods; Elementary School Curriculum; Intergroup Education; Declaration of Independence